Marketing Management Strategies of Buffalo Livestock Traders in Addressing Price Fluctuations at Bolu-Rantepao Animal Market - Isak Pasulu; Elisabet Pali; Elsap Patta Pasulu; Johanna R. Tangirerung (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study explores marketing management strategies employed by buffalo livestock traders at the Bolu-Rantepao Animal Market, North Toraja, in addressing extreme price volatility shaped by cultural and seasonal factors. Responding to a significant research gap in marketing practices within culturally embedded traditional markets, this study adopts a qualitative descriptive approach using case study methodology. Data were collected through in-depth interviews, participant observation, and document analysis with four purposively selected informants operating in high-volume buffalo trade. Analysis reveals that successful traders implement integrated marketing systems comprising five key components: market intelligence for predictive planning, product portfolio management through quality and segment differentiation, dynamic value-based pricing strategies, multi-channel distribution optimization, and customer relationship management (CRM) for loyalty and premium pricing leverage. These strategies enable traders to navigate volatile market dynamics, especially during ceremonial demand spikes such as the Rambu Solo. The findings highlight that adaptive execution, systematic planning, customer orientation, and feedback-driven improvements are central to marketing success. This study contributes to marketing theory by contextualizing modern management principles in traditional commodity markets and offers practical insights for strategic development in rural livestock economies. It also suggests digital adoption and CRM systems as key leverage points for future competitiveness in similarly structured markets across developing countries.